Sistem Informasi Manajemen Penjualan untuk Optimalisasi Lead Time Pelayanan Konsumen Menggunakan Metode Waterfall di CV. Buana Jaya Sentosa - Siti Khadijah; Bibit Sudarsono (JOURNAL SAINS STUDENT RESEARCH, 2026)
Buana Jaya Sentosa is a company engaged in the food wrapping and packaging industry, which still uses manual recording for its sales processes. This situation causes various operational obstacles, such as lengthy administrative processes, data recording errors, and communication barriers between departments. These problems directly impact long customer service lead times and reduce service quality. This study aims to implement a sales management information system as a solution to the problems of the manual sales process and to optimize customer service lead times. The system development method used is the Waterfall method, which includes the stages of needs analysis, system design, implementation, and system testing. Data collection techniques were conducted through observation, interviews, and documentation studies at CV. Buana Jaya Sentosa. The results of this study are a sales management information system that has been implemented and is able to support an integrated sales process. The system developed includes product data management, sales transaction recording, automatic stock checking, and digital transaction document generation. Based on the system implementation results, transaction processes are faster, recording errors are minimized, and customer service lead times are optimized compared to the previous manual system.